Distribution of Fatty Acids in A Seedling Almond Population and Their Mutual Relationships - ÇELIK*, FERIT; BALTA†, FIKRI; DOGAN, ADNAN; JAVIDIPOUR‡, I.; KAZANKAYA†, AHMET (Asian Journal of Chemistry, 2024)
This paper deals with determining kernel fatty acid contents basedon oil distribution in a seedling almond population consist of 90 seedlingtrees from Turkey and mutual relationships among fatty acids. Almondpopulation was divided into three groups based on the range of fat contents.Genotypes averagely contained 6.70 % palmitic acid, 0.57 % palmitoleicacid, 1.78 % stearic acid, 72.83 % oleic acid, 18.03 % linoleic acid,0.15 % linolenic acid and 0.39 % myristic acid. In addition, they had91.58 % unsaturated fatty acid content, 8.87 % saturated fatty acid contentand 10.32 unsaturated/saturated ratio. Findings of this study indicatethat contents of oleic and linoleic acids were influenced by the range ofoil in the seedling population.